2021
DOI: 10.46237/amusbfd.738738
|View full text |Cite
|
Sign up to set email alerts
|

Günübirlik Cerrahi Sonrası Ağrı Yönetiminde Hemşirelik Yaklaşımı

Abstract: Ayaktan cerrahi olarak da bilenen günübirlik cerrahinin kullanımı her geçen gün artmaktadır. Günübirlik cerrahi sonrası bazı istenmeyen durumlar arasında ağrı yer almaktadır. Multidisipliner ekip anlayışı ile yönetilmesi gereken ameliyat sonrası ağrı, hastaların günlük bakımından sorumlu olmalarından dolayı hemşireleri merkezi bir konuma getirmektedir. Günübirlik cerrahi sonrası ağrı yönetimi, ameliyat öncesi bilgi ve eğitim vermeyle başlamaktadır. Ameliyat öncesi eğitim, hastanın durumuna ve yapılan cerrahiye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This may affect the quality of care given to the patient. 7 The quality of care administered by nurses is very important for a successful day surgery. Wongkietkachorn et al reported that needsbased education given to patients undergoing day surgery increased patient satisfaction, reduced anxiety and shortened the time allocated for education.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may affect the quality of care given to the patient. 7 The quality of care administered by nurses is very important for a successful day surgery. Wongkietkachorn et al reported that needsbased education given to patients undergoing day surgery increased patient satisfaction, reduced anxiety and shortened the time allocated for education.…”
mentioning
confidence: 99%
“…8 Nurses should evaluate and provide effective care in a very short time with their own experience and knowledge to the patient who will undergo day surgery. [6][7][8][9][10] It is essential to reveal the factors affecting the fear and to make care plans in this direction in order to make an appropriate intervention for the fears of the patients in the pre-surgical period. 6,11 In this context, the determination of the fear levels of day surgery patients and the affecting factors, which are increasing all over the world, can guide the nurses who will provide health care services in a limited time period in the preoperative psychological evaluation of the patient.…”
mentioning
confidence: 99%